Polystyrene‐based anion exchange membranes via click chemistry: improved properties and AEM performance. Issue 9 (4th July 2018) - Tuli, Sayema K; Roy, Asa L; Elgammal, Ramez A; Zawodzinski, Thomas A; Fujiwara, Tomoko
ABSTRACT: Polystyrene‐based anion exchange membranes (AEMs) have been fabricated using in situ click chemistry between azide and alkyne moieties introduced as side groups on functionalized polymers. The membrane properties such as water uptake, swelling ratio and conductivity were affected by the number of cations and the degree of crosslinking. The membranes containing a larger amount of trimethylammonium cationic groups (i.e. higher ion exchange capacity) showed high hydroxide conductivity when immersed in KOH solution, exhibiting a peak in conductivity (156 mS cm −1 ) in 3 mol L –1 KOH solution. A higher degree of crosslinking tended to decrease conductivity. These membranes demonstrated relatively good stability in 8 mol L –1 KOH at 60 °C and maintained 33%–62% of initial conductivity after 49 days with most of the loss in conductivity occurring in early stages of the test. In an alkaline fuel cell, the areal specific resistance was constant indicating good stability of the membranes. The observed peak power density (157 mW cm −2 ) was comparable to that of other AEM‐based fuel cells reported. © 2018 Society of Chemical Industry Abstract : Polystyrene‐based anion exchange membranes crosslinked by click chemistry between functionalized side groups exhibited improved hydroxide conductivity and relative stability. The anion exchange membrane showed constant areal specific resistance and comparable power density in an alkaline fuel cell.